Seasonal and monthly variations of protein content in the muscle of fish Schizothorax esocinus - Jan, Ulfat; Shah, Mustafa; Manzoor, Tahila; Ganie, Showkat Ahmad (Recent Research in Science and Technology, 2012)
Schizothorax esocinus (Chirruh snow barbell) Heckel, 1838 a key and freshwater species in the valley of Kashmir and is now endangered one. This study is to evaluate seasonal and monthly changes in protein content of muscle tissue and was studied over a period of twelve months from January 2011-Febuary 2012. Remarkable variation in protein content of muscle tissues of S. esocinus has been analyzed during the study period. The protein content of fish species showed increased level in summer season (28%) and lowest percentage in winter season (10%), attaining peak values in July (35%) and minimum value in December (0.08%). The results indicate that the protein content of the fish depends on season but also to a great extent in reaction to food and reproductive cycle. The present study is the first to describe the seasonal variation in the protein content of muscle of Schizothorax esocinus from the Kashmir Valley.